Ethical dilemmas of social worker – student of social work - Nádvorníková, Lenka (Univerzita Pardubice, 2010)
The report describes possible ethical problem situations or dilemmas arising during professional performance of social worker who is at the same time student of the combined form of the first degree study program of social work. The author of this report purposely deals with several selected articles of The Ethical Codex of social workers in the Czech Republic, which she compares with students´ opinions of the study programme above mentioned acquired from evaluative questionnaires, and with her own observations from the pedagogic practice.
Keywords: ethical dilemma; ethical codex of social workers in the Czech Republic; combined form of study; qualifying readiness; professionalism of social worker; career field